Impact of climate change on agricultural production and agroclimatic conditions in the Pirot valley - Nataša Martić Bursać; Ljiljana Stričević; Milena Gocić (Economic Themes, 2024)
This research is motivated by the fact that climate change has significantly impacted various facets of the environment and society in recent decades. One of the most vulnerable sectors to climate change is agriculture, as it heavily relies on weather conditions. The rise in global temperatures and the increasing frequency of extreme weather events have triggered significant changes in plant life, impacting their physiology, distribution, and abundance. Together, these factors result in alterations in the agroclimatic conditions of agricultural production. The objective of this study is to investigate whether similar changes are present in the Pirot valley, given that climatic conditions, alongside geographic location and soil quality, are critical for successful cultivation of crops and achieving high yields. The analysis utilizes data from the Republic Hydrometeorological Service of Serbia for Pirot meteorological station spanning the period 1961-2020. A comprehensive analysis was conducted on monthly and annual temperature and precipitation patterns, accompanied by an assessment of agroclimatic indices and their trends. Furthermore, a comparative analysis of two standard climatological periods, 1961-1990 and 1991-2020, demonstrated the evident impact of climate change, directly influencing the quality, quantity, and overall development of agriculture in the Pirot Valley.
Keywords: G01; G12; G19; 330; climate change; agriculture; agroclimatic conditions; Pirot Valley